Education and Training for Information Science in India - Rajan, T. N. (Journal of Information and Knowledge, 1978)
Traces the genesis of education and training for documentation and information science in India. Examines the courses of DRTC and INSDOC relating to curriculum design, teaching methodology and materials, practical work, project work and dissertation, the products turned out and their performance. Mentions the contributions of the universities with particular reference to the Department of Library Science of the Delhi University. Briefly describes the continuing education programmes and short courses. Indicates the variety of manpower force required for the future and the training needed for it.